Acquisition and synthesis of folates by obligate intracellular bacteria of the genus Chlamydia. - Fan, H (1992)
We undertook studies focused on folate acquisition by Chlamydia trachomatis L2, Chlamydia psittaci 6BC, and C. psittaci francis. Results from in situ studies, using wild-type host cells, confirmed that C. trachomatis L2 and C. psittaci 6BC are sensitive to sulfonamides whereas C. psittaci francis is resistant. In addition C. trachomatis L2 and C. psittaci francis were inhibited by methotrexate in situ whereas C. psittaci 6BC was not. In contrast to C. trachomatis, neither C. psittaci strain was affected by trimethoprim. Surprisingly our results indicate that all three strains are capable of efficient growth in folate-depleted host cells. When growing in folate-depleted cells C. psittaci francis becomes sensitive to sulfonamide. The ability of all three strains to carry out de novo folate synthesis was demonstrated by following the incorporation of exogenous [3H]pABA into intracellular folates and by detecting dihydropteroate synthase activity in reticulate body crude extract. Dihydrofolate reductase activity was also detected in reticulate body extract. In aggregate the results indicate that C. trachomatis L2, C. psittaci francis, and C. psittaci 6BC can all synthesize folates de novo, however, strains differ in their ability to transport preformed folates directly from the host cell.